Building Trust in AI -A Simplified Guide to Ensure Software Quality - Devalla, Sahithi; Yogi, Manas Kumar (Journal of Soft Computing Paradigm, 2023)
In recent years, Artificial Intelligence (AI) has emerged as an innovative technology in a variety of areas, including software development. The demand for high-quality software has grown in tandem with the increasing complexity of applications and user expectations.AI-driven approaches are revolutionizing traditional software development methodologies by automating and augmenting various stages of the development life cycle, leading to improved efficiency, reduced costs, and enhanced software quality. This research explores the crucial role of AI in developing high-quality software and its impact on the software development process. Firstly, it discusses how AI technologies like machine learning, natural language processing, and deep learning can facilitate requirements gathering, analysis, and validation, leading to better understanding and refinement of user needs. Next, it delves into the significance of AI in automating the coding process, such as generating code snippets, fixing bugs, and optimizing performance, thus accelerating development and reducing human errors. Moreover, the paper highlights the pivotal role of AI in software testing and quality assurance. AI-powered testing tools can execute comprehensive tests more efficiently, detect defects, and predict potential software vulnerabilities, thereby enhancing the overall reliability and robustness of the software product. Additionally, AI techniques can enable real-time monitoring and analytics, allowing developers to identify and address issues promptly during the software's operational phase. Furthermore, the paper addresses the ethical considerations and challenges associated with AI in software development, including bias in training data, interpretability of AI-driven decisions, and potential job displacement for software developers.
Keywords: AI; Quality; Defect; Improvement; Process